The Clinical Manifestations and Genetic Implications of Baraitser–Winter Syndrome Type 2 - Allawh, Tanya C.; Brown, Barry Scott (Journal of Pediatric Genetics, 2017)
An 18-year-old Caucasian male was born by cesarean section weighing 2.6 kg (5 lb 14 oz) at birth after an uncomplicated pregnancy with no perinatal complications. Around 4 to 5 months of age, the patient's mother initially became concerned as he was experiencing signs of developmental delay and a mild floppy tone, in addition to facial features that resembled some form of mental retardation. The patient's older brother also experienced similar developmental symptoms and facial features that presented around the same age period as our patient. It was initially thought to be Down syndrome; however, both the patient and his brother tested negative for Down syndrome on chromosomal analyses. There was also a question of whether the patient had some form of autism spectrum disorder, but doctors were unable to specifically confirm this. Now at the age of 18 years, the patient has no understandable speech with distinctive facial features such as a broad nasal bridge and prominent epicanthic folds, lissencephaly, smaller than average head size, intellectual disability, and hearing loss. It was discovered, through trio-based exome sequencing, that the patient had a de novo missense mutation (p.Ser155Phe) in the ACTG1 gene, which has been linked to the rare syndrome known as Baraister–Winter syndrome type 2. Baraitser–Winter syndrome 2 is a unique variant that is clinically similar to Baraitser–Winter syndrome type 1; however, only seven previous cases have been reported.
Keywords: Baraitser–Winter syndrome type 2; ACTG1 gene mutations; de novo